Analysis of Bread Lipids for 3-MCPD Esters - M. Doležal; J. Kertisová; Z. Zelinková; J. Velíšek (Czech Journal of Food Sciences, 2009)
Objective of this work was determination of processing contaminant known as 3-MCPD (3-chloropropane-1,2-diol) in its free and bound form in breads with defined parameters of processing. Selected and analysed were 24 samples, which represented two sets of breads produced in bakeries equipped with a continual line. In all cases determinations were carried out for breadcrumb and crust separately. The first set of samples were wheat-rye breads produced chronologically in ten days in the bakery Michelská pekárna, slightly different in temperatures and times of baking. The second set contained 14 samples of wheat-rye breads with a content of rye flour less than 40% differing in the yeast type and acidity. These breads were produced in the bakery Kontinua. The fat content was determined in all samples by Soxhlet extraction. Free and bound 3-MCPD was determined by gas chromatography-mass spectrometry method. Concentration of free 3-MCPD in samples was at interval < 9-54.5 μg/kg. Concentration of bound 3-MCPD was at interval 1.56-23.60 mg/kg of fat (i.e. 5.7-84.9 μg/kg of sample).